RANCANG BANGUN SISTEM INFORMASI INVENTARIS PERALATAN TEKNOLOGI INFORMASI DI SWISSBEL HOTEL DANUM PALANGKARAYA - Felicia Sylviana; Abertun Sagit Sahay; Nano Ridhansyah (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2016)
Swiss-bel Hotel Danum Palangkaraya is one of the hotels located in Palangkaraya. The development of the hotel business increased to make every company in the business want to provide a best for employees to work and customers who come to stay. These goals would make any equipment related to Information Technology (IT) should be able to operate smoothly and quickly in order to achieve a hotel corporate in Palangkaraya who actively and creatively trying to meet the needs of consumers both in terms of quality, value, and customer satisfaction. It required the Inventory Information Systems of IT equipment that can record and manage IT equipment, making it easier to know the condition of IT equipment and IT equipment maintenance schedule.In the Inventory Information System development of IT equipment in the Swiss-bel Hotel Danum Palangkaraya using waterfall method. In this methodology is done several steps to build a software, namely analysis, design, coding, testing and maintenance. In step modeling analysis using Unified Modeling Language (UML). UML model used is the Use Case Diagrams, Activity Diagrams and Class Diagrams. The programming language used is PHP and the MySQL databaseThis research has resulted in the application of IT Equipment Inventory Information System in the Swiss-bel Hotel Danum Palangkaraya which has features to manage IT equipment, IT equipment maintenance schedules, user applications and reports. Reports generated as department detailed reports, inventory reports, reports of maintenance schedule of IT equipment, reports of conditions and specifications of IT equipment every department, every month, by year of acquisition, location, and date of last maintenance IT equipment.